2019
DOI: 10.1177/2158244019861485
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Teaching Through Interactions and Pupils’ Learning in Mathematics

Abstract: The aim of the study is to map patterns of teaching quality through interactions in Mathematics lessons in lower secondary school classrooms. The sample is 10 ninth-grade classrooms in Norway (pupils’ age, 14-15 years). Reciprocal linkages between teaching through interactions in Mathematic lessons and pupils’ results on a standardized National Curriculum Mathematic Test, before and after observed lessons ( N = 115) over 7 months, are studied. To map quality of teacher–pupil interactions in classrooms, observa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
5

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 43 publications
2
19
0
5
Order By: Relevance
“…However, the results showed that analysis and inquiry, the dimension for higher-order questions, problem-solving and metacognition, was the dimension with lowest score in the instructional support domain, consistent with previous studies (e.g. Gamlem, 2019;Westergård et al, 2019). This points to difficulties in facilitating opportunities for selfregulation by attention to students' internal feedback through classroom dialogues as conceptualised in responsive pedagogy (Smith et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…However, the results showed that analysis and inquiry, the dimension for higher-order questions, problem-solving and metacognition, was the dimension with lowest score in the instructional support domain, consistent with previous studies (e.g. Gamlem, 2019;Westergård et al, 2019). This points to difficulties in facilitating opportunities for selfregulation by attention to students' internal feedback through classroom dialogues as conceptualised in responsive pedagogy (Smith et al, 2016).…”
Section: Discussionsupporting
confidence: 88%
“…The concept of responsive pedagogy encompasses a feedback practice that is concerned with activating students as active agents of their own learning processes (Smith et al, 2016;Vattøy & Smith, 2019). Teachers (and peers) are identified as significant others in responsive pedagogy, as they are important facilitators of learning processes (Gamlem, 2019).…”
Section: Teacher-student Interactions and Feedback In Efl Classroomsmentioning
confidence: 99%
See 2 more Smart Citations
“…The original research by and was followed by hundreds of studies in the field. The last studies in the field conclude that students' interactions during peer tutoring have positive significant effects on students' mathematics learning (Gamlem, 2019;Alegre, Moliner, Maroto & Lorenzo-Valentin, 2019a). Several literature reviews and meta-analysis have documented the academic benefits of this methodology across all educational levels, from Early Childhood Education to College .…”
Section: Introductionmentioning
confidence: 99%